2005
DOI: 10.3758/bf03196048
|View full text |Cite
|
Sign up to set email alerts
|

Transposition in pigeons: reassessing spence (1937) with multiple discrimination training

Abstract: We studied transposition in pigeons, using multiple-pair discrimination training. Four birds discriminated two pairs of circles: 1+ 2- and 5+ 6- or 1 - 2 + and 5- 6 + (digits denote circle diameters and plus and minus signs denote reward and nonreward, respectively). Four other birds discriminated four pairs of circles: 1+ 2-, 1+ 3-, 4+ 6-, and 5+ 6- or 1- 2 +, 1- 3 +, 4- 6+, and 5- 6+. Finally, 4 birds discriminated only one pair of circles: 1+ 2-, 1- 2+, 5+ 6-, or 5- 6+. Testing included five new pairs--1/5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
59
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 55 publications
2
59
1
1
Order By: Relevance
“…Testing included two stimulus pairs for which, according to theoretical postdiscrimination generalization gradients, transposition should decrease from one-pair to two-pair to three-pair training. On the basis of the results of our earlier study (Lazareva, Wasserman, & Young, 2005) and contrary to these predictions, we expected that transposition should increase from one-pair to two-pair to three-pair training. We found that multiple-pair discrimination training enhanced transposition, which, on average, rose from 47% (one-pair training) to 52% (two-pair training) to 64% (three-pair training).…”
contrasting
confidence: 43%
See 3 more Smart Citations
“…Testing included two stimulus pairs for which, according to theoretical postdiscrimination generalization gradients, transposition should decrease from one-pair to two-pair to three-pair training. On the basis of the results of our earlier study (Lazareva, Wasserman, & Young, 2005) and contrary to these predictions, we expected that transposition should increase from one-pair to two-pair to three-pair training. We found that multiple-pair discrimination training enhanced transposition, which, on average, rose from 47% (one-pair training) to 52% (two-pair training) to 64% (three-pair training).…”
contrasting
confidence: 43%
“…Beyond these results, Lazareva et al (2005) found in subsequent experiments that pigeons' transposition responses rose from one-to two-to four-pair discrimination training along the size dimension, thus replicating and extending the findings of Johnson and Zara (1960). Can an increase in transposition after an increase in the number of training pairs be predicted from excitatory and inhibitory stimulus generalization gradients?…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…For this reason, any test involving stimuli that are not too far removed from the S+ or the S-may produce what can be interpreted as relational responding, so-called transposition. This associative account is problematic for the development of a relational class, because the generalization of absolute values may pro-vide a more parsimonious interpretation of such responding than a relational interpretation (see Lazareva, Wasserman, & Young, 2005 for a critical discussion of these issues and new data which challenge Spence's classical account).…”
Section: Relational Classesmentioning
confidence: 99%